Geodynamic evolution of the São Fidelis -Santo António de Pádua sector, central Ribeira Fold Belt, SE Brazil - Santos,T. M. Bento dos (2009)
New structural analysis and petrological results on granulites from the central segment of Ribeira Fold Belt indicate that the regional thrusts D1 (245-260° , 55-70° NW) was coeval with the high grade peak metamorphism at 565 - 575 Ma, post-dating earlier collision related nappe thrusts at 630 - 610 Ma (D0). These were mostly erased by D2 thrusting and long-term dextral transpressional shearing (50-65° , 70-85° NW), simultaneous with very slow cooling of the orogen until 480 - 520 Ma. Brittle, extensional, tectonic event D3 (290-320° , subvertical) is associated with late granite emplacement in the area, being followed by tectonic collapse that resulted in rapid exhumation/cooling of the high grade rocks at ~ 470 Ma. Results suggest that a > 35 Ma period of nearly orthogonal shortening between the San Francisco and West Congo cratons occurred until 565 Ma with development of the D1 flower thrust system. Afterwards, when rocks could not absorb further orthogonal shortening, D2 dextral transpressive regime became dominant, turning the flower structure asymmetric. Specific positioning within the flower structure and partition of deformation induced local antithetical sinistral kinematics within the main regional dextral regime and differential exhumation: granulites in the central axis were rapidly exhumed, whereas along the lateral branches exhumation was much slower resulting in very slow cooling that lasted for almost 100 Ma.